2015
DOI: 10.7314/apjcp.2015.16.14.5613
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Optimal Detection of Cancer by Image Processing; Experience with Lung and Breast Cancers

Abstract: Clinicians should looking for techniques that helps to early diagnosis of cancer, because early cancer detection is critical to increase survival and cost effectiveness of treatment, and as a result decrease mortality rate. Medical images are the most important tools to provide assistance. However, medical images have some limitations for optimal detection of some neoplasias, originating either from the imaging techniques themselves, or from human visual or intellectual capacity. Image processing techniques ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Image processing techniques have shown success in improving cancer diagnosis through several mechanisms. Recent advances have been made into classifying histopathological images of malignancies (Mohammadzadeh et al 2015); machine learning algorithms have shown to be promising tools (Benzheng Wei et al 2017;Komura and Ishikawa 2018;Dimitriou et al 2019;Iizuka et al 2020). Apart from microscopy, other sources of images have also yielded possible means for diagnosing several types of cancers, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Image processing techniques have shown success in improving cancer diagnosis through several mechanisms. Recent advances have been made into classifying histopathological images of malignancies (Mohammadzadeh et al 2015); machine learning algorithms have shown to be promising tools (Benzheng Wei et al 2017;Komura and Ishikawa 2018;Dimitriou et al 2019;Iizuka et al 2020). Apart from microscopy, other sources of images have also yielded possible means for diagnosing several types of cancers, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is a major cause of death in the world with high health priority and has become an important issue in public health. [1][2][3] According to GLOBOCAN 2012 estimations, there were about 14.1 million new cancer cases, 8.2 million cancer deaths and 32.6 million people who living with cancer (within 5 years of diagnosis) in 2012 worldwide. 4 Occupational cancer is occurred due to exposure to many environmental and occupational factors including biological, chemical and physical carcinogens.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is not only a personal disease and beside its great influences on many aspects of patient life (Abbasnezhad et al, 2015); it has socioeconomically impacts (Cannon et al, 2012). Raise individual awareness about cancer leads to prevention and early detection of cancer and reduce mentioned costs (Mohammadzadeh et al, 2015). Patients with cancer desire to obtain updated information about different aspects of their disease such as sign and symptoms, diagnosis, treatment, side effects of various methods of treatment, follow up and cancer effect on their life (Shahrokni et al, 2013).…”
Section: Introductionmentioning
confidence: 99%